Influenza vaccination reduces cardiovascular events in patients with acute coronary syndrome - Arintaya Phrommintikul (2018)
Aims Influenza infection has been shown to accentuate the progression of atherosclerosis and precipitate the occurrence of acute coronary syndrome (ACS). However, the protective effects of the influenza vaccine on cardiovascular events are still inconclusive. Methods and results The study was a prospective randomized open with blinded endpoint (PROBE) study. The 439 patients who had been admitted due to ACS within 8 weeks were enrolled and randomly allocated to receive inactivated influenza vaccine in the vaccine group and no treatment in the control group. All patients were treated with the standard therapy including revascularization according to primary cardiologists. The primary endpoint, which was the combined major cardiovascular events, including death, hospitalization from ACS, hospitalization from heart failure, and hospitalization from stroke, occurred less frequently in the vaccine group than the control group [9.5 vs. 19.3%, unadjusted HR 0.70 (0.57-0.86), P = 0.004]. There was no significant difference in the incidence of cardiovascular death between the vaccine and control groups [2.3 vs. 5.5, unadjusted HR 0.39 (0.14-1.12), P = 0.088]. Conclusion The influenza vaccine reduced major cardiovascular events in patients with ACS. Therefore, it should be encouraged as a secondary prevention in this group of patients. © 2011 The Author.